Self-care with non-prescription medicines to improve health care access and quality of life in low- and middle-income countries: systematic review and methodological approach - May, Uwe; Bauer, Cosima; Schneider-Ziebe, Anissa; Giulini-Limbach, Chiara (Frontiers in Public Health, 2023)
Objectives: This study aims to develop a structured framework to capture beneficial effects and determine the value of self-care for individuals and society in low-and middle-income countries (LMICs). A special focus is placed on self-medication with non-prescription medicines.Methods: PubMed, Google Scholar and websites of associations or organizations were systematically searched for economic studies on self-care and self-medication published between 2000 and 2021. The insights gained from the literature review were incorporated into the development of a decision tree model.The literature review revealed a lack of research and available data on the role and value of self-care in LMICs. To help close the research gap a methodological framework was developed that defines different settings of self-care, their effects and relevant outcomes and allows a quantification with regard to self-medication in LMICs.Self-care offers individuals a convenient and reliable way to take care of their own health, especially in LMICs where access to health services can be challenging. In particular it is crucial to improve individuals access to clinically effective, safe and reliable non-prescription medicines.